Rekonstruksi dan Reaktualisasi Literasi Ekologi Sosial Islam - Heru Kurniawan (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
Literacy on Islamic social ecology is the human interaction with the natural environment, technology, and social which is based on the basic principles of Islam. Reconstruction of literacy on Islamic social ecology that can be reconstructed is a basic tenet of Islam that affirms the human position as a